The historical uncanny : disability, ethnicity, and the politics of Holocaust memory - Knittel, Susanne C. (Fordham Univ. Press, 2015)
Introduction -- Part I -- Remembering euthanasia : Grafeneck as heterotopia -- Bridging the silence, part I : the disabled enabler -- Bridging the silence, part II : the vicarious witness -- Interlude -- Lethal trajectories : perpetrators from Grafeneck to the Risiera -- Part II -- Black holes and revelations : the Risiera, the foibe, and the making of an "Italian tragedy" -- A severed branch : the memory of fascism on stage and screen -- Bridging the silence, part III : Trieste and the language of belonging -- Conclusion